NON-METRIC VARIATIONS OF THE AXIAL SKELETON BONES IN MEDIEVAL SKELETONS FROM VINICA FORTRESS (VINICHKO KALE) - Matveeva, Niki; Veljanovska, Fanica; Zhivadinovikj, Julija; Zafirova, Biljana; Chadikovska, Elizabeta; Dodevski, Ace; Trpkovska, Biljana; Bojadzieva Stojanoska, Biljana (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2021)
The majority of researchers use cranial and infracranial non-metric traits as separate entities in their investigations of the past populations. We decided to focus our investigation on the axial skeleton non-metric traits, consisting of components such as cranial and vertebral columskeleton. The main goal of our study was to gain some insight into the expression of axial skeleton non-metric traits in a medieval population sample. We investigated 72 well preserved skeletons from the medieval period documented collection (11-12 century AD) in order to examine axial skeleton non-metric traits. The skeletons belonged to individuals aged 20 to 65 years, of both sexes, exhumed from the necropolis Vinichko Kale. Analysis of cranial non-metric traits in our population sample showed a high prevalence of occipital bone cranial traits, such as os apicis (13.9%) and torus occipitalis (20.8%). Among vertebral column non-metric traits, a high prevalence of cervical spine traits, such as ponticulus posterior atlantis (11%), foramen transversarium partitum - FTP (33.3%), foramen transversarium apertum - FTA (13.9%) and cervical ribs (13.9%) was noted. Our findings of skeletal non-metric traits in the medieval population can provide additional knowledge in the skeletal growth and development in general.
Keywords: osteology; archeology; anatomical variations; axial skeleton